ABO Blood groups in relation to duodenal ulceration among the Yorubas of western Nigeria. Issue 4 (December 1963) - Davey, W. W.; Elebute, E. A.
Abstract : This paper shows that in Nigeria as in England there is an excess of blood group O in patients with duodenal ulcer.